Study of siliceous outcrops of Meseta del Fresco, La Pampa, Argentina - Carrera Aizpitarte, Manuel Pedro (2015)
This paper introduces the results of the study of the silicifications from Meseta del Fresco (Fresco Formation), a vast source of chert in La Pampa province (Argentina), that was widely used by hunter-gatherer groups from the Pampas as a source of raw material. Petrographic analysis of different thin sections, both from geological samples from different parts of the unit, as well as from cultural material associated with the outcrops, was performed. The objective that guided these studies was to develop a detailed description of the type of siliceous replacement upon the prior rock (limestone) and from the filling of its cavities.The results obtained let us inquire about the nature and origin of silicification, about the diversity depending on the location in the profile of the carbonate rock replaced during the diagenetic process, and about the extent to which this process affected the Fresco Formation at various points sampled. From an archaeological perspective, the analysis constitutes an advance in the study of lithic resources procurement behaviors developed by hunter-gatherer societies in the past because: 1) a database about the characteristics and variations of the silicification present in the outcrop was generated, as a tool to compare the archaeological samples from different sites, 2) different degrees of rock silicification that could favor its aptitude for knapping, were tested. This could have motivated preferential selection for making lithic artifacts. The archaeological information recorded in different sites on the eastern and western slopes of Meseta del Fresco is quantified in order to show the differential use of both areas.